Faktor Sosial Budaya dalam Praktik Perawatan Kehamilan, Persalinan, dan Pasca Persalinan (Studi di Kecamatan Bangsri Kabupaten Jepara) - Suryawati, Chriswardani (Jurnal Promosi Kesehatan Indonesia, 2007)
Background : Reproductive health is focusing on the reproductive aspect of women which are considerable problems on sexuality and reproduction, such as ante-natal care, delivery process, postpartum treatment etc. Maternal mortality rate and infant mortality rate are some indicatorsof reproductive health, where in Indonesia those rate are still high rather than some neighboring countries. Previous research showed that socio-cultural and demographic factors influence the high maternal and infant mortality rate. The purpose of this study was to describe sociocultural aspect towards ante-natal care, delivery process and post –partum treatment among Javanese.Method: The design study was observational with cross sectional approach. The research took place in Jepara Region, Central Java. The population study was women in reproductive age and total number of the sample was 60 women. Data were collected through questionnaire using in – depth interview guide. Socio- cultural factors data were gathered through in-depth interview with health providers, such as doctors, midwives as well as religious people and community leader.Results: This study found that the majority of the respondents (96.7%) did antenatal care, assisted by doctors or midwifes, accompanied by their husband (76.6%), done every month (48.3%). Midwife is health provider who was mostly chosen by respondents furthermore by traditional birth attendance (18,4%). The accompanying reasons were the distance between the home and the location, skill and the complete of the apparatus. Most of the respondent (93%) accompanied by their husband during birth process. During post- partum period, they took traditional medicine and also massage. This study found that there is no special food has been consumed during antenatal and post-partum period. Ritual activities have done such as mitoni (munari), krayanan (brokohan), resikan (walikan) and kekahan (aqiqah) since pregnancy until post-partum period.Keywords : Antenatal care, Reproductive health, Postpartum